1992
DOI: 10.1029/92ja01138
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic electron microbursts

Abstract: We report the first satellite observations of relativistic (>1 MeV) electron precipitation in microbursts with measured durations of less than 1 s. Microbursts of lower-energy electrons (10-100 keV) have been found to occur preferentially in the early daylight hours and to be closely associated with VLF chorus emissions. In contrast, the relativistic electron microbursts occurred more frequently near 2230 LT than 1030 LT, and no association was found with ELF/VLF chorus, consistent with the fact that resonant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 18 publications
3
68
1
Order By: Relevance
“…On the other hand, Imhof et al (1992) and Nakamura et al (2000) reported observations of impulsive electron precipitation with energies >1 MeV on polar orbiting spacecraft and called them relativistic microbursts (Blake et al, 1996;O'Brien et al, 2004). It is known that relativistic microbursts are associated with large amplitude whistler mode waves (Johnston and Anderson, 2010;Kersten et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Imhof et al (1992) and Nakamura et al (2000) reported observations of impulsive electron precipitation with energies >1 MeV on polar orbiting spacecraft and called them relativistic microbursts (Blake et al, 1996;O'Brien et al, 2004). It is known that relativistic microbursts are associated with large amplitude whistler mode waves (Johnston and Anderson, 2010;Kersten et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Microbursts were later shown to extend to relativistic energies (Imhof et al 1992), and studied extensively with data from the SAMPEX satellite (e.g., Blake et al 1996;Nakamura et al 2000;). The top panel of Fig.…”
Section: Types Of Relativistic Electron Precipitationmentioning
confidence: 99%
“…The timescales of chorus waves are similar to those of electron microbursts, and the coincident occurrence of microbursts and VLF chorus waves supports the idea that microbursts are produced by resonant interactions between electrons and cyclotron waves (Rosenberg et al 1981). Imhof et al (1992) and Nakamura et al (2000) reported observations of impulsive electron precipitations with energies exceeding 1 MeV by spacecraft; these precipitations were named relativistic microbursts. However, relativistic microbursts have not been observed by balloon-borne experiments, and at this time it is unknown whether these microburst phenomena are related or originate from the same source.…”
Section: Introductionmentioning
confidence: 55%